Real-Life Management of Diabetic Macular Edema with Dexamethasone Intravitreal Implant: A Retrospective Analysis of Long-Term Clinical Outcomes. (10th April 2020) - Nicolò, Massimo; Musetti, Donatella; Marenco, Maria; Cotti, Lorenzo; Bonetto, Monica; Giacomini, Mauro; Traverso, Carlo Enrico
Abstract : Purpose . Inflammation plays a key role in the pathogenesis of diabetic macular edema (DME), and intravitreal corticosteroids are among the recommended therapies. The goal of this retrospective analysis was to describe outcomes with dexamethasone intravitreal implant (DEX implant) in real life. Methods . Medical digital records of DME patients treated with DEX implant and followed up for 3 years were analyzed. Treatment with DEX implant was started either as first-line therapy in pseudophakic patients and in patients with cardiovascular comorbidities or as second-line therapy in patients refractory to the inhibitor of the vascular endothelial growth factor (anti-VEGF) therapy. Analyzed outcomes included central macular thickness (CMT) and best-corrected visual acuity (BCVA). Mean number of implant injections per patient and mean duration of the interval between injections were also estimated. Results . Seventy-five patients (mean age 65.7 (±12.3) years; 53 phakic and 22 pseudophakic) with DME were included. Overall, 84 eyes were treated. Mean CMT improved from 380.1 (±100.3) µ m at baseline to 306.8 (±77.0) µ m at 36 months (p = 0.0003 ). Mean BCVA improved for up to 6 months (p = 0.08 ) and then started to decrease reaching values lower than baseline after 24 months. In pseudophakic patients, BCVA improvements were more pronounced and sustained up to 36 months (p = 0.6 ). Over 36 months, each patient received on average 2.4 (±1.6) intravitreal injections of DEX implant. The time interval between consecutive injections was included between 180 and 240 days. No unexpected safety issues were reported. Conclusions . With fewer than 3 injections per patient over a 3-year period, DEX implant was able to improve anatomic outcomes in DME patients. Only pseudophakic eyes showed also a long lasting functional benefit at 36 months.